Using website information to reduce postpurchase dissonance: A mediated moderating role of perceived risk. Issue 1 (24th September 2020) - Li, Mingfang; Choudhury, Askar H.
Abstract: A significant body of research is dedicated to decreasing the product return rate by applying management measures that identify the factors and causes of returns. These studies examine how consumers' product return behavior can be explained by studying the information on retailers' websites. However, these studies have not shown how website information (WI) is linked to product returns. The study by Lee's work observed how product returns are motivated by consumers' need to mitigate postpurchase dissonance (PPD). However, a clear understanding of the relationship between WI and PPD is lacking. Therefore, our research examines the impact of WI on PPD in the product returns context. In our research, PPD serves as a key factor in understanding the linkage between WI and product returns. Our results showed that higher‐quality WI is associated with a lower level of PPD. In addition, a lower perceived risk (PR) or attractiveness of alternatives strengthens the association between WI and PPD. We also observed that PR partially mediated the moderation effect of the attractiveness of alternatives. These findings will help e‐retailers better understand customers' PPD, easing the process of reducing product returns.